Anti-C5 Antibody Tesidolumab Reduces Early Antibody-mediated Rejection and Prolongs Survival in Renal Xenotransplantation. Issue 3 (September 2021) - Adams, Andrew B.; Lovasik, Brendan P.; Faber, David A.; Burlak, Christopher; Breeden, Cynthia; Estrada, Jose L.; Reyes, Luz M.; Vianna, Rodrigo M.; Tector, Matthew F.; Tector, Alfred J.
Abstract : Objective: Pig-to-primate renal xenotransplantation is plagued by early antibody-mediated graft loss which precludes clinical application of renal xenotransplantation. We evaluated whether temporary complement inhibition with anti-C5 antibody Tesidolumab could minimize the impact of early antibody-mediated rejection in rhesus monkeys receiving pig kidneys receiving costimulatory blockade-based immunosuppression. Methods: Double (Gal and Sda ) and triple xenoantigen (Gal, Sda, and SLA I) pigs were created using CRISPR/Cas. Kidneys from DKO and TKO pigs were transplanted into rhesus monkeys that had the least reactive crossmatches. Recipients received anti-C5 antibody weekly for 70 days, and T cell depletion, anti-CD154, mycophenolic acid, and steroids as baseline immunosuppression (n = 7). Control recipients did not receive anti-C5 therapy (n = 10). Results: Temporary anti-C5 therapy reduced early graft loss secondary to antibody-mediated rejection and improved graft survival ( P < 0.01). Deleting class I MHC (SLA I) in donor pigs did not ameliorate early antibody-mediated rejection (table). Anti-C5 therapy did not allow for the use of tacrolimus instead of anti-CD154 (table), prolonging survival to a maximum of 62 days. Conclusion: Inhibition of the C5 complement subunit prolongs renal xenotransplant survival in a pig to non-human primate model.